An Information Theory Analysis of the Accounting Process. - Lee, Lucy C.; Bedford, Norton M. (The Accounting Review, 1969)
Abstract The bookkeeping procedures have been described as an information process of data collection, classification, tabulation, summarization, and presentation. The accounting classification and measurement function tends to be overlooked due to the clerical work involved in it. The financial state of the firm is continuously changing, of course, because of the occurrence of economic events. It is the accountant's function to recognize their effect on the financial state. A general accounting process may be described as a means of achieving the decision-making end of an accounting information user. This paper centers on the first part of the process-the information formation process, a process by which the accounting classification and measurement function determines the effect of an economic event on a firm's financial state. A communication channel model is used to describe the accounting classification function as the link between the various economic events of a firm and its financial state. The accounting channel of classification may be deterministic, lossless, or noisy as defined in information theory.